Integrity of Women’s Bodies: The Urgency of Protecting Women from Catcalling as a Form of Symbolic Violence - Lusiana Margareth Tijow; Rotua Valentina Sagala; Akhsanul Khaq; Bobur Sobirov (Jurnal Hukum, 2026)
Catcalling has emerged as a pervasive form of symbolic violence in Indonesian public spaces, threatening women’s bodily integrity and limiting their freedom of movement. This study aims to analyze catcalling as an expression of patriarchal culture that reduces women’s bodies to sexual objects, examines its psychological, social, and physical impacts on victims, and evaluates gaps in the Indonesian legal system regarding verbal sexual harassment. Despite the harmful consequences, current regulations often fail to explicitly address verbal harassment in public spaces, and such behaviors are frequently considered trivial or tolerated as part of local customs. This research employs a normative and comparative legal approach, examining both Indonesian laws and international best practices to identify lessons that can inform more effective legal protections. The study also explores institutional mechanisms necessary to safeguard women’s rights and dignity. The findings indicate that catcalling contributes to fear, anxiety, trauma, and prolonged stress among women, reinforcing unsafe conditions and perpetuating gender inequality. The study underscores the urgent need for comprehensive, gender-just legal reforms that explicitly criminalize verbal harassment, provide adequate remedies for victims, and promote public awareness.